Symmetric and Positive Definite Broyden Update for Unconstrained Optimization - Saad et al. (مجلة بغداد للعلوم)
Broyden update is one of the one-rank updates which solves the unconstrained optimization problem but this update does not guarantee the positive definite and the symmetric property of Hessian matrix.